Imatinib Metabolism and Disposition in Isolated Rat Perfused Liver: Imatinib Metabolism and Disposition in Isolated Rat Perfused Liver - Shiva Moghtadaee; Yalda H. Ardakani; Hoda Lavasani; Mohammad-Reza Rouini (Iranian Journal of Pharmaceutical Sciences, 2016)
Imatinib is an orally administered tyrosine kinase inhibitor which inhibits the Bcr-Abl protein-tyrosine kinase with high selectivity. Imatinib is rapidly absorbed from the gut, after oral intake and has an almost absolute bioavailability of 98%. The metabolism of imatinib is mediated by the cytochrome P450 (CYP) isoenzymes in the liver and gut wall. CGP74588 is a major active metabolite of imatinib. The study was performed on Male Sprague-Dawley rats (250-300 g) housing under artificial light on a 12-h light/dark cycle with free access to standard laboratory chow and water. Re-circulating (at imatinib concentration of 1 and 5 μg/ml) and single-pass (imatinib dose of 1mg) perfusion modes in the presence and absence of BSA were tested. Throughout the experiment, perfusate temperature (37± 0.5 C°), pH (7.4±0.2) and liver viability (ALT and AST) were monitored. The concentrations of imatinib and its main metabolite in perfusion buffer and liver homogenate were determined by a validated HPLC method.No metabolite was detected in outlet perfusate in all conditions. However, negligible amounts of metabolite were found in liver homogenate at 1 and 5 μg/ml imatinib concentrations in re-circulating perfusion mode. The rapid and remarkable disappearance of imatinib from perfusate was related to its accumulation in liver. Statistical moment definition was used to calculate some pharmacokinetic parameters. These calculations also confirmed liver accumulation and slow and sustained dissociation of imatinib from liver.